Proprioception following the Anterior Cruciate Ligament Reconstruction with Tibialis Anterior Tendon Allograft - Büyükafşar, Enes; Başar, Selda; Kanatli, Ulunay (The Journal of Knee Surgery, 2020)
After the anterior cruciate ligament (ACL) reconstruction, a loss of proprioception is observed and it can continue years after the operation. The aim of this study is to evaluate proprioception in standing position at different knee flexion angles in patients who underwent ACL reconstruction with tibialis anterior tendon allograft. The study included 34 patients who underwent ACL reconstruction with tibialis anterior tendon allograft and 34 healthy individuals. Proprioception was evaluated in standing position at 15°, 30°, 60° flexion angles with the active joint position sense (AJPS) method using digital inclinometer. Proprioception deviation angle was found to be higher in the operated leg at 30° and 60° flexion angles in the patient group compared with the other leg (p < 0.05), the biggest proprioception difference was between the 15° and 60° flexion angles in both the patient and the control group (p < 0.05) that the difference between 15° and 30° flexion angles is lowest (p < 0.05), and that these differences are higher in the operated leg of the patient group compared with the other leg of the patient group and to the dominant leg of the control group (p < 0.05). As approximately 4 years after ACL reconstruction with tibialis anterior tendon allograft, loss of proprioception at 60° knee flexion continued, ACL injury related to loss of proprioception may occur at angles higher than 30° flexion. Thus, patients may be provided with proprioception-enhancing rehabilitation in the long term, particularly, at flexion angles above medium levels.
Keywords: knee surgery; arthroscopy; rehabilitation; proprioception